The Emergence of the Obscured: A Study of Abandoned Villages in Paphos District - Sofokleous, Nikoleta; Philokyprou, Maria (Technical Annals, 2025)
The present research focuses on abandoned villages in Paphos, Cyprus – an area with the highest concentration of such settlements on the island. The study aims to identify and recognise these deserted villages, analyse the reasons for their abandonment and evaluate their historical and cultural significance. By examining population data, maps and archival resources spanning 1881 to 2011, the research offers a detailed understanding of the district’s evolution and the challenges these areas face today. Moreover, it reveals a complex interplay of factors driving abandonment, including urbanisation, economic hardship, isolation, environmental degradation, as well as historical and political events. This multifaceted approach highlights the unique cultural and social dimensions of these abandoned settlements’, positioning them as vital elements of Cyprus’s heritage. Methodologies such as demographic analysis, geographical mapping and comparative research with earlier studies offer actionable insights. These findings underscore the urgent need for legislative reform and interdisciplinary collaboration to protect and preserve the settlements. By offering a holistic view of the abandonment phenomenon, the research provides a framework for developing effective management strategies that can be applied both locally and internationally. The ultimate goal is to safeguard these invaluable cultural assets for future generations.